2016
DOI: 10.1016/j.juro.2015.10.116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Holmium Laser Prostate Enucleation Outcomes in Patients with or without Preoperative Urinary Retention

Abstract: This study represents the first direct comparison to our knowledge of holmium laser prostate enucleation outcomes in patients with or without urinary retention. There was no increased risk of postoperative urinary retention in patients with preoperative retention, and both groups demonstrated significant postoperative improvement in subjective and objective voiding measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…In a comparison study between urinary retention patients and patients who could void spontaneously before HoLEP, perioperatively the urinary retention group had a lower blood transfusion rate and did not require long-term recatheterization. 27,28 Postoperatively, peak urinary flow was higher in men without urinary retention at 6-and 12-month follow up, but similar to men with initial urinary retention at longer follow up. Taken together, HoLEP is a good tool for addressing urinary retention in men, with a 100% rate of postoperative spontaneous voiding and no differences in the complication rate.…”
Section: Urinary Retentionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a comparison study between urinary retention patients and patients who could void spontaneously before HoLEP, perioperatively the urinary retention group had a lower blood transfusion rate and did not require long-term recatheterization. 27,28 Postoperatively, peak urinary flow was higher in men without urinary retention at 6-and 12-month follow up, but similar to men with initial urinary retention at longer follow up. Taken together, HoLEP is a good tool for addressing urinary retention in men, with a 100% rate of postoperative spontaneous voiding and no differences in the complication rate.…”
Section: Urinary Retentionmentioning
confidence: 76%
“…reported that all patients in their series were voiding spontaneously after HoLEP without major complications. In a comparison study between urinary retention patients and patients who could void spontaneously before HoLEP, perioperatively the urinary retention group had a lower blood transfusion rate and did not require long‐term recatheterization . Postoperatively, peak urinary flow was higher in men without urinary retention at 6‐ and 12‐month follow up, but similar to men with initial urinary retention at longer follow up.…”
Section: Urinary Retentionmentioning
confidence: 94%
“…26,27 Peterson et al reported on their experience with 164 men undergoing HoLEP for urinary retention 27. Following HoLEP, all patients were voiding spontaneously and no major complications were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Following HoLEP, all patients were voiding spontaneously and no major complications were reported. A more contemporary series compared the outcomes of 95 patients in urinary retention to 136 men who were voiding spontaneously prior to HoLEP 26. Perioperatively, men in urinary retention were less likely to require a blood transfusion (1.0% vs 4.4%, P =0.01).…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no significant difference in the decrease in hemoglobin levels and transfusion need [36]. Since the development of urinary retention depends on obstruction operations due to BPH, various studies that investigated the reliability of HoLEP indicated that functional outcomes were the same in both patients that developed and did not develop postoperative recurrent retention [37, 38]. Although HoLEP was determined to be reliably performed in patients with bladder stones among pathologies requiring surgical treatment, the number of studies is limited [39], which should be researched.…”
Section: Discussionmentioning
confidence: 99%